Generation and detection of acoustic waves in microwave cavities - ALEKSIEJUK, M.; PAJEWSKI, W. (Archives of Acoustics, 1995)
This paper containes a detailed analysis of the conditions of acoustic wave excitation in retrant-type, microwave cavities, obtained by means of the methods field. Dependence of the resonance frequency on the resonator parameters and the material constants of a piezoelectric sample placed in the resonator is given. Construction of the resonators investigated and the experimental data concerning their parameters in the 0.210 GHz frequency range are presented. Results of attenuation measurements of waves in lithium niobate and bismuth-germanium oxide crystals obtained by applying the resonators described are also shown.